Youth are united online to fight against involution: a study of group cohesion on Weibo - Zhang, Yang; Ji, Tong (Frontiers in Psychology, 2023)
Background: In China, involution, which means pressure to out-compete other group members, has attracted public attention on Weibo. The new online connotation of involution empowered group cohesion among youth. Dissimilar to other crises, this crise also closely relates to group cohesion concept. However, few previous group cohesion-related studies focus on this critical concept. This study explains why and how youth created group cohesion online when facing involution. First, by examining the relationship between involution and group cohesion. Second, by examining whether youth are united in the online discussion of involution by investigating the generational gap. Following this, this study analyzes the different opinions to identify why this group cohesion occurs, how youth think about involution, and why they regard “older adults” as others. Lastly, this study analyzes how youth use hashtags to attract more youth to voice their opinions, consequently leading to greater group cohesion. Methods: By combining frontier computational methods with causation and axial coding, this study proposes a new way to in-depth analyze group cohesion on social media. Results: The results indicate that involution triggers poor online group cohesion, and online involution-related hot issues trigger identity-based group cohesion. Additionally, youth are significantly more negative than older adults, and their expressions are full of identity-based construction. By stressing the social roots and blaming the “other” (older adult group), youth united together online. These findings indicated that a generation gap does indeed exist and that youth unite on social media by posting related hashtags via “revealing social identity” and “positioning and becoming” strategies. Conclusions: The findings stress that involution is related to poor group cohesion and that social media offers a new way to face the involution crisis. Youth will use hashtags to unite and blame imagined enemies, such as older adults and the upper class. These findings might assist in understanding interventions that lead to more group cohesion.